Characterization of Small-Molecule-Induced Changes in Parkinson's-Related Trafficking via the Nedd4 Ubiquitin Signaling Cascade. Issue 1 (21st January 2021) - Hatstat, A. Katherine; Ahrendt, Hannah D.; Foster, Matthew W.; Mayne, Leland; Moseley, M. Arthur; Englander, S. Walter; McCafferty, Dewey G.
Summary: The benzdiimidazole NAB2 rescues α-synuclein-associated trafficking defects associated with early onset Parkinson's disease in a Nedd4-dependent manner. Despite identification of E3 ubiquitin ligase Nedd4 as a putative target of NAB2, its molecular mechanism of action has not been elucidated. As such, the effect of NAB2 on Nedd4 activity and specificity was interrogated through biochemical, biophysical, and proteomic analyses. NAB2 was found to bind Nedd4 (KD app = 42 nM), but this binding is side chain mediated and does not alter its conformation or ubiquitination kinetics in vitro . Nedd4 co-localizes with trafficking organelles, and NAB2 exposure did not alter its co-localization. Ubiquitin enrichment coupled proteomics revealed that NAB2 stimulates ubiquitination of trafficking-associated proteins, most likely through modulating the substrate specificity of Nedd4, providing a putative protein network involved in the NAB2 mechanism and revealing trafficking scaffold protein TFG as a Nedd4 substrate. Graphical Abstract: Highlights: NAB2 binds to Nedd4 with apparent affinity in the nanomolar range NAB2 treatment does not induce changes in Nedd4 activity or conformation in vitro α-Synuclein toxicity drastically changes global protein ubiquitination NAB2 treatment of toxic cells reveals novel Nedd4 target and trafficking network Abstract : N- Arylbenzdiimidazole ligand NAB2 was previously shown to rescue Parkinson's-related toxicity in cellular models in a manner dependent upon E3 ubiquitin ligase Nedd4. Here, Hatstat et al . report a biochemical and proteomic characterization of the NAB2 mechanism, advancing our understanding of NAB2 and Nedd4 as anti-parkinsonian lead and target, respectively.